PALYNOLOGICAL RECORD OF CLIMATE CHANGE DURING THE LAST DEGLACIATION FROM THE SONG HONG (RED RIVER) DELTA, VIETNAM - Li Z.; Matsumoto E.; Wang Y.; Saito Y.; Haruyama S.; Hori K.; Doanh L.Q. (My University, 2006)
The palynological sequence from core ND-1 on the Song Hong delta in the northern Vietnam reveals the climate change during the last deglaciation. The identified pollen in the core is dominated by Castanopsis (Lithocarpus), Elaeocarpus, Ficus, Piperaceae and Quercus. High percentages of temperate taxa including the conifers Dacrydium, Podocarpus, Pinus, Cupressaceae, Txodiaceae and Cryptomeria, and broad-leaved taxa of Carpinus, Alnus, Juglans, Carya, Ulmus, Fagus, Ilex, Castanea, Quercus, which have a mainly upland distribution, is possibly associated with a lowering of the montane vegetation boundary. On the other hand, intensified river influence can also result in an increase in the temperate allochthonous taxa. After analyzing the magnitude of river influence on pollen assemblages during the sedimentary environment evolution, we extracted the climate information and used this to reconstruct climate change during the last deglaciation. A cooler climate during 14.5-10.9 cal. kyr BP than at present is indicated by higher percentage of temperate types than at present under a similar river influence on the floodplain. The Younger Dryas cooling event is recognized by widely developed grasslands between 12.9 and 11.6 cal. kyr BP, adding to the evidences for this period from both terrestrial and marine records in regions influenced by the East Asian monsoon. Two other cooling periods, 9.4-9.0 cal. kyr BP and 6.5-5.2 cal. kyr BP, are indicated by increases of temperate pollen taxa such as Cryptomeria, Alnus, Quercus, and Castanea. © 2005 Elsevier B.V. All rights reserved.
Keywords: CLIMATE CHANGE; LAST DEGLACIATION; PALYNOLOGY; SEDIMENTARY ENVIRONMENT; SONG HONG (RED RIVER) DELTA